Mengevaluasi Kewajiban Negara Pada Umat Hindu Di Kudus Jawa Tengah - Moh. Rosyid (Jurnal Penelitian Agama Hindu, 2020)
This article was written to evaluate the role of government and Kudus government to service for Hindus in Kudus. Data of this research was gathered through interview, forum group discussion, observation and descriptive qualitative approach. There are several things can be done by Kudus government: (1) facilitating the establishment of puraas a worship place for Hindus in Kudus, (2) recruiting teacher for Hinduism in schools, (3) enacting bylaws on informal religious education for all religions. These policies are actually continuing the spirit of tolerance, the legacy of Sunan Kudus. Respecting people despite their religion and ethnic is a manifestation of faith in God.